Writing to Speaking: Using Journal Writing as a Scaffold to Gain Confidence in L2 Speaking - Manalo, Nesiel O. (International Journal of Research in Interdisciplinary Studies, 2024)
In the Philippines, quite a number of educational institutions are still very strict about the English only Policy (EOP). Students, teachers, staff and stakeholders are prescribed to use the English language as a medium of communication, and non-compliance to this would me a violation of the rule. However, students in a community whose first language is not English, poses a resisting behavior towards the use of the language. Researchers have found that a possible explanation to this is the fact that the speakers lack the faculty to use the language. Though many Filipinos have regarded a certain prestige to this language, one cannot discount the fact that using it in a community with different L1 creates an uncomfortable feeling towards students whose language of everyday communication is not English. In order to address this concern, I would like to look into the possibility of utilizing writing as a scaffold for confident oral communication.